Mass Civic Festivity in the Confrontation with the Everyday - Rapoportas, Sergejus (Sociologija. Mintis ir veiksmas, 1997)
During the period of Lithuania’s revival and the restoration of independence (1988-1991) the streets and the squares were in use for mass events, which substantially differed from everyday life as well as from Soviet mass rituals. The socio-ontological content of the recent events remains of special value. The forms mass coexistence are often presented in an abstract form: as self-contained reality (folk, nation and etc.) or as a ‘statistical habitats’. Yet the movements present a different case: an interrelation between private lives in the public events. The article discusses how certain type of discourse, namely voluntary political ritual, is being created and understood.
Keywords: movement of indepence; mass events; voluntary political ritual; the everyday